ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU BERAS DENGAN METODE EOQ PADA LUSI KULINER - Mukti, Wisnu Wardana; Pradana, Bayu Ilham (Jurnal Kewirausahaan dan Inovasi, 2022)
The objective of his research is to analyze rice stock inventory using Economic Order Quantity (EOQ) method for the optimization of stock cost at Lusi Kuliner. This descriptive quantitative research discusses issues in the research object as they are, and Economic Order Quantity was selected as the solution. The informants of this research are employees who know all of the company’s operational and marketing processes. This study finds that the use of economic order quantity, safety stock, and reorder point can optimize rice stock inventory costs and make the schedule of rice stock purchasing schedule more organized.